Pemberdayaan Kader Lansia Melalui Program "KADER CERIA" di Posyandu Lansia Wilayah Kerja Puskesmas Mlati II - Amirah Salwa; Nur Hidayat; Siti Budi Utami (Media Gizi Kesmas, 2026)
Background: Diabetes mellitus is a non-communicable disease that often affects the elderly and requires long-term management, including dietary regulation. The cadres at Integrated Service Posts (Posyandu) play an important role in providing education to the elderly, but their capacity to deliver it is often limited. Objectives: This study aimed to improve cadres’ knowledge and skills in providing nutritional education to elderly individuals with diabetes mellitus through training and the use of flipchart media in the “KADER CERIA” empowerment program. Methods: This study used a Participatory Action Research design with a mixed method approach. This research was conducted at Posyandu Plaosan Village and Posyandu Bakalan Village, located in the working area of Mlati II Public Health Center, Sleman Regency, Special Region of Yogyakarta, in September–November 2025. Data collection involved measuring cadres’ knowledge before and after training, assessing their skills after training, and conducting in-depth interviews to explore their perceptions and experiences of the program. The training was delivered by the researcher, with support from health workers, and conducted in a single session. Quantitative data were analyzed univariately and bivariately, while qualitative data were analyzed through data reduction, presentation, and conclusion drawing. Results: Cadres’ knowledge increased significantly before and after training (p=0.000), with the mean knowledge score rising from 55.20 to 88.40. Cadres stated that flipcharts were easy to use, helped deliver education, and increased cadres’ confidence when interacting with the elderly. The cadres also hoped that similar training would be conducted on an ongoing basis and that the material would be expanded to include other degenerative diseases. Conclusion: The flipchart-based nutrition education training was effective in improving cadres’ knowledge, skills, and confidence, and in supporting their empowerment as health education agents in the community.